Adverse Drug Reactions in Children: Comparison of Reports Collected in a Pharmacovigilance Project Versus Spontaneously Collected ADR Reports - Leitzen, Sarah; Dubrall, Diana; Toni, Irmgard; Stingl, Julia; Christ, Patrick; Koberle, Ursula; Schmid, Matthias; Neubert, Antje; Sachs, Bernhardt (Paediatric Drugs, 2022)
Background: Adverse drug reactions (ADRs) and medication errors in children may result from a lack of appropriate drugs, dosages, and pharmaceutical forms. In addition, children may respond differently to drugs than adults. Reporting of ADRs in the pediatric population is therefore of importance in order to increase the amount of safety data. However, different methodological approaches are used to collect ADRs. Objective: The aim of the present study was to analyze whether there were differences in the ADRs collected in the KiDSafe project (845 ADR reports) compared with the spontaneous ADR reports sent to EudraVigilance (697 reports) in the same time period. The strengths and limitations of these two different approaches should be discussed. Methods: The same inclusion criteria were applied for the systematically collected ADRs in the KiDSafe project and the spontaneous reports from EudraVigilance, and only reports of ADRs coded with hospitalization were considered. In both datasets, the number of reports (related to number of hospitals), their documentation quality (VigiGrade), causal relationship (World Health Organization-Uppsala Monitoring Centre [WHO-UMC] criteria), most frequently reported drugs and ADRs, demographical parameters of the patients, reported medical histories, and the seriousness of ADR reports were analyzed descriptively. The results of the two analyses were compared. Results: There was considerable underreporting of ADRs via the spontaneous reports (0.4 reports per hospital; 697/1902) compared with 70.4 reports per hospital (845/12) in the systematically collected KiDSafe reports. Documentation quality assessment yielded similar results in both datasets. Among the 10 most frequently reported drugs, anticonvulsants such as levetiracetam (6.6%), valproic acid (5.6%), oxcarbazepine (3.6%), and lamotrigine (3.4%) were mainly reported in the KiDSafe reports, while in the EudraVigilance reports, mite allergen extract (4.4%) and allergens (3.6%) were preferentially reported. Seizures were the most frequently reported clinically specific ADRs in the KiDSafe reports, whereas anaphylactic reactions and urticaria were prominent in the spontaneous reports from EudraVigilance. Notably, the proportion of reports referring to medication errors and other medication safety related issues were more prominent in KiDSafe than in the spontaneous reports (27.8% vs. 12.6% and 46.0% vs. 29.0%, respectively). Conclusion: In general, reports from both data sources contributed to the identification of ADRs and dedicated issues related to drug therapy. However, these differed by nature and strength of the signal, likely due to the characteristics of the individual method. A combined approach could likely compensate for limitations inherent to the single approaches, but will most likely only be applied to dedicated pharmacovigilance topics or research objectives.
CRIS-Team Scopus Importer:2022-11-25